USE OF INTERACTIVE FLAT PANEL DISPLAY (IFPD) MEDIA IN SOCIAL STUDIES LEARNING FOR MADRASAH STUDENTS - Tutuk Ningsih; Rachman Riyadi (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2024)
The development of increasingly advanced technology has a very rapid impact on all aspects of people's lives, including in the fields of knowledge and education. Technology in the field of education is one of the supporting media for the implementation of education itself, one of which is the use of Interactive Flat Panel Display (IFPD) media. The purpose of this study is to examine more deeply the use of Interactive Flat Panel Display (IFPD) media in Social Studies Learning for Madrasah Students. This research was conducted at Madrasah Ibtidaiyah Darwata Sikampuh, with the research subjects being teachers and fifth-grade students, and the research object of the use of IFPD in social studies learning. This research is a qualitative descriptive research, with the type of field research (Filed Research). Data collection is carried out by means of observation, interviews, and documentation. Data analysis was carried out using the Miles Huberman technique by reducing data first, presenting the data that had been reduced, and drawing conclusions and verification. The results of this study show that the use of IFPD media at MI Darwata Sikampuh is carried out through several stages, starting from the planning stage, the resource and media stage, the stage of using IFPD media and the learning evaluation stage. The impact of using IFPD in learning has various positive impacts on the student learning process, namely increasing student involvement and participation, increasing motivation and interest in learning, facilitating understanding of complex concepts, increasing collaboration and cooperation, increasing creativity and technological skills, improving critical and analytical thinking skills, accelerating feedback and evaluation, increasing adaptability in learning, improving digital literacy skills, reducing boredom in learning.